0966 Dipping Pattern of Nocturnal Blood Pressure and Depressive Symptoms. (27th April 2018) - Thomas, R J; Kim, H; Yun, C; Kim, S; Kim, E; Lee, S; Shin, C
Abstract: Introduction: Diurnal patterns of blood pressure (BP), as measured by 24-h ambulatory blood pressure monitoring (ABPM), has been widely used as a measure of vascular function, with nocturnal BP dipping pattern as a critical indicator for various health outcomes. Following a circadian rhythm, nocturnal BP drops by 10–15% from the daytime BP, and the absence of this pattern has been a risk factor for conditions such as stroke and cardiovascular diseases. Recent studies also link depression with poor cardiovascular outcomes, but any association between depression and ABPM remains undefined. The current study was conducted to examine the link between nocturnal BP dipping pattern and depressive symptoms in a large-scale, community-based sample. Methods: The study sample was consisted of 1, 914 participants (mean age=60.4, 46.9% female) from the Korean Genome and Epidemiology Study (KoGES). 24-hour ABPM was administered to all participants, and BP dipping patterns were defined as the ratio of the change in night-time and daytime systolic blood pressure. Based on the dipping patterns, participants were categorized into Dippers (nocturnal SBP dipping ≥10%), Non-Dippers (dipping= 0–10%), and Reverse-Dippers (dipping≤ 0%). Depressive symptoms were measured using the Beck Depressive Inventory (BDI), and depression was determined with BDI>13. Results: Non-Dippers and Reverse-Dippers consisted of 39.9% and 13.7% of the study sample, respectively. The BDI score was significantly different across the groups, with Reverse-Dippers displaying the highest BDI (9.69 ± 7.7), followed by Non-Dippers (8.1 ± 7.3) and Dippers (7.5 ± 6.8). The results remained statistically significant after adjusting for covariates (age, sex, education, hypertension medication, diabetes, and activity) in the ANCOVA model. Post-hoc analysis revealed a significantly higher BDI score in the Reverse-Dippers compared to Dippers, but not Non-Dippers (p<0.05). Additionally, multiple logistic regression revealed that Reverse-Dippers had an increased odds of depression compared to Dippers (OR=1.8, 95% CI=1.3–2.5). Conclusion: Depression scores were significantly different by BP dipping status, with Reverse-Dippers displaying the highest depressive symptoms. Compared to Dippers, Reverse-Dippers had an almost twofold increased prevalence of depression. Our results indicate a strong association between abnormal BP pattern and mood disorders. Support (If Any): Grant 2011-E71004-0, 2012-E71005-00, 2013-E71005-00, 2014-E71003-00.